Pattern of Pelvic Malignancies - Gul-e-Lala, Naheed Akhtar, Shakira Noreen, (Journal of Rawalpindi Medical College, 2014)
Background: To determine the frequency of various gynaecological malignancies and to describe the age distribution, stage and clinical presentation of various gynaecological malignancies. Methods: In this descriptive study all patients with Gynecological malignancies were included in the study irrespective of the age and stage of the diseases.Patients with breast cancer associated with Pelvic Cancer were excluded from the study.Clinical data was collected from the patients by taking history and performing relevant examination and filling up the attached questionnaire/ performa. Results: There were 15 cases with ovarian cancer, nine of cervical cancer, three cases of endometrial cancer, two cases of vulvar cancer and one case of chorio carcinoma. Age of the patients with cervical cancer ranged from 45-67 years. Endometrial cancer presented at mean age of 56 years. In ovarian cancer age of patients ranged from 24-63 years. The mean age of patients with vulvar cancer was 72.5 years. The age of the patient with choriocarcinoma was 32 years. Weight loss, vaginal bleeding and discharge, menstrual irregularities, post menopausal bleeding were common clinical manifestations . Most of the patients, in all types, presented in late stages. Conclusion: Patients with gynecological malignancies have good prognosis, if cancer is detected at an early stage. Therefore efforts should be made to encourage women to seek medical advice at first abnormal symptom.